Maintaining market principles: Government auditors, PPP equity sales and hegemony. Issue 1 (April 2017) - Smyth, Stewart; Whitfield, Dexter
Abstract: The UK's government auditors, the National Audit Office (NAO), play a central role in the accountability relations surrounding government expenditure. Commonly portrayed as being independent, they carry out performance audits assessing value for money. To date, the emerging market for PPP equity transactions has attracted little attention. This paper explores that emerging market through a Gramscian framework utilising the concepts of 'common sense' and 'good sense', focusing on a dialogical analysis of a NAO report on the topic. In the process, the paper contributes to the debate about the nature and role of government auditors.